2021
DOI: 10.3389/fpls.2021.768717
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient Dosing Framework for an Emission-Free Urban Hydroponic Production

Abstract: The urban hydroponic production system is accelerating industrialization in step with the potentials for reducing environmental impact. In contrast, establishing sustainable fertilizer dosing techniques still lags behind the pace of expansion of the system. The reproducibility of root-zone nutrient dynamics in the system is poorly understood, and managing nutrients has so far primarily relied on periodic discharge or dumping of highly concentrated nutrient solutions. Here, we assayed root-zone nutrient concent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…So far, standard nutrient solutions have been developed to consider each nutrient requirement ratio, chemical stability, and yield of plants through plant nutritional studies [27][28][29][30]. Even though previous standard nutrient solutions were developed with information about nutrient requirement ratios, the input nutrient ratios for a steady state could be different from predictions because of nonlinear ratio change in nutrient uptake [31]. While previous studies have observed nutrient changes that could be interpreted as a steady state [32][33][34], they have not discussed results in terms of a steady-state control technique.…”
Section: Nutrient Concentration Changesmentioning
confidence: 99%
“…So far, standard nutrient solutions have been developed to consider each nutrient requirement ratio, chemical stability, and yield of plants through plant nutritional studies [27][28][29][30]. Even though previous standard nutrient solutions were developed with information about nutrient requirement ratios, the input nutrient ratios for a steady state could be different from predictions because of nonlinear ratio change in nutrient uptake [31]. While previous studies have observed nutrient changes that could be interpreted as a steady state [32][33][34], they have not discussed results in terms of a steady-state control technique.…”
Section: Nutrient Concentration Changesmentioning
confidence: 99%
“…According to Ahn et al (2021) and Christie (2014), there are two methods in the nutrient-dosing system for hydroponic plant cultivation. The first method uses a sensor to read concentrations and mix nutrients with fresh water to form a ready-to-use nutrient solution.…”
Section: Introductionmentioning
confidence: 99%
“…The sensors are based on electrical conductivity (EC), whose value correlates with the nutrient concentration level. According to Ahn et al, (2021), the use of the EC sensor method causes the proportion of nutrient absorption to be known based on the nutrients absorbed periodically. In addition, this method can also eliminate two unknown variables: transpiration and variations in total nutrient absorption.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, matching nutrient supply with special nutritional needs of the crop (Gianquinto et al, 2013;Signore et al, 2016) involves some difficulties with this technique because nutrient addition dosage is not directly related to the nutrient composition of the drainage. An ideal approach should be to continuously monitor individual nutrients in the recycled solution (e.g., ion-selective sensors), however, such techniques are not available in commercial practice up to now (Ahn et al, 2021). The integration of simulation and sensing tools with actual measurements and different management strategies has been documented to be effective in theory and practice in soilless crops (Massa et al, 2020).…”
Section: Introductionmentioning
confidence: 99%